Preoperative masked renal damage in Japanese patients with primary aldosteronism: Identification of predictors for chronic kidney disease manifested after adrenalectomy. (27th November 2012) - Utsumi, Takanobu; Kawamura, Koji; Imamoto, Takashi; Nagano, Hidekazu; Tanaka, Tomoaki; Kamiya, Naoto; Nihei, Naoki; Naya, Yukio; Suzuki, Hiroyoshi; Ichikawa, Tomohiko
<x xml:space="preserve">Abstract</x> Objective Correct interpretation of renal function in patients with primary aldosteronism is difficult before adrenalectomy, because subtle kidney impairment is often masked by glomerular hyperfiltration peculiar to primary aldosteronism. The aim of this study was to investigate postoperative changes in renal function for patients with primary aldosteronism and to identify clinical predictors of chronic kidney disease manifested postoperatively in the patients without pre‐existing chronic kidney disease. Methods Records of 78 Japanese patients who underwent unilateral adrenalectomy for primary aldosteronism were retrospectively surveyed. Patients who had been followed up for <6 months were excluded. Preoperative and postoperative estimated glomerular filtration rate were compared. Furthermore, uni‐ and multivariate analyses were carried out to identify clinical predictors for chronic kidney disease manifested postoperatively. Results Patients with preoperative estimated glomerular filtration rate ≥60 mL/min/1.73 m2 showed a significant decrease after surgery. Of the 66 patients without pre‐existing chronic kidney disease, 24 developed chronic kidney disease postoperatively. Multivariate logistic regression analysis identified a medical history of dyslipidemia as an independent predictor for chronic kidney disease manifested postoperatively. According to univariate analyses, additional factors associated with postoperative manifestation of chronic kidney disease included older age, lower diastolic blood pressure and lower estimated glomerular filtration rate. Conclusions The interpretation of normal or abnormal renal functions by examining estimated glomerular filtration rate heightened by hyperfiltration alone can mislead clinicians before adrenalectomy. Clinicians should pay attention to patients at greater risk of a significant decline in postoperative renal function.